Lack of Correlation of the Serum 25(OH) Vitamin D Levels with the Glycated Hemoglobin A1c and the Lipid Profile in Type 2 Diabetes Patients on Oral Antidiabetic Drugs – Preliminary Data - Bakalov D. (Sciendo, 2014)
Data from different studies correlating the serum 25(OH)D levels with the metabolic and glycemic parameters in type 2 diabetes patients are still varying. The objective if this study was to describe the correlation between serum 25(OH)D levels and some metabolic parameters in Bulgarian type 2 diabetes patients on oral antidiabetic drugs. One hundred type 2 diabetes patients participated - 56 men and 44 women. The mean age and diabetes duration of the women was 59.0 and 9.8 years, of the men - 58.0 and 7.7 years respectively. Complete patient history was taken and physical examination was performed (body weight and height, waist circumference). Body composition was measured on a leg-to-leg body impedance analyzer (TBF-215, Tanita Corp., Tokyo, Japan). Serum levels of vitamin D were measured by electro-hemi-luminescent detection as 25-(ОН) D Total (ECLIA, Elecsys 2010, Roche Diagnostics, Switzerland). Glycated hemoglobin A1c was measured on a NycoCard reader (Alere™). Total, HDL-cholesterol (direct) and triglycerides were analyzed on a Cobas Integra 400+ analyzer. Correlation analysis was performed on a SPSS 13.0 for Windows platform and included 10 curves. The data were first analyzed for the group as a whole and then separately for men and women as well as in the different vitamin D tertiles. The mean serum 25-OH-vitamin D levels were 23.8 ± 12.1 nmol/l in women and 33.3 ± 20.0 nmol/l in men. We were unable to find any statistically significant correlation between serum 25(OH) vitaminand the serum lipids (cholesterol profile and triglycerides). On the contrary, there was a weak correlation with the glycated hemoglobin A1c (cubic model, R2 = 0.178, p = 0.05) and the BMI (inverse model, R2 = 0.101, p = 0.038). The sub-analyses (men versus women or according to tertiles of vitamin D) did not produce any additional information. The influence of vitamin D on the parameters of the metabolic control in type 2 diabetes is very weak on an individual level. It might be only demonstrated in large epidemiological surveys.